Historical-Cultural Activity Theory and Grounded Theory as Methodologies for Investigating Teacher Identity: A Systematic Review - Cárcamo, Benjamín (2024)
Teacher identity has gained global attention as a construct of interest due to its potential to explain teacher attitudes and behaviors. Despite this growing interest, few studies have explored the implementation of qualitative methodologies in the empirical study of teacher identity. The objective of this study was to investigate how Cultural-Historical Activity Theory (CHAT) and Grounded Theory (GT) are utilized in empirical research on teacher identity. To achieve this, we followed the PRISMA model guidelines for systematic reviews, establishing inclusion and exclusion criteria for the bibliographic search, such as publication date and the nature of the research. The final analysis included 31 research articles. The results identify patterns in the objectives, data collection techniques, and analysis methods used in both approaches within the context of empirical studies on teacher identity.